PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Putri, Andini; Syahrul Rizal, Muhammad; Ananda, Rizki; Nurhaswinda, Nurhaswinda; Fitra Surya, Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking skills of fourth-grade students in Civics Education at UPT SD Negeri 004 Salo. The purpose of this research was to determine the effect of the Problem Based Learning (PBL) model on students’ critical thinking skills compared to the Discovery Learning model. This research employed an experimental method with a Quasi-Experimental Nonequivalent Control Group Design. The sample consisted of class IVB as the experimental group and class IVA as the control group. Data were analyzed using an independent t-test with the assistance of SPSS 24.0. The results showed that the average pretest score of the experimental class was 54.00, which increased to 70.33 on the posttest, while the control class increased from 54.83 to 58.50. The significance value of the t-test was 0.016 < 0.05, indicating a significant difference in students’ critical thinking skills between the experimental and control classes. Therefore, it can be concluded that the implementation of the Problem Based Learning model has a significant effect on improving students’ critical thinking skills in Civics Education at UPT SD Negeri 004 Salo.